AKUNTABILITAS DAN TRANSPARANSI: Kunci Sukses Manajemen Keuangan Kebijakan Pendidikan Gratis di Yayasan Ahmad Syamsul Ma’arif Langgongsari - Erna Malia Rofikoh (TSURAYYA: Journal Education, Economy and Religia, 2026)
The purpose of this study is to find out about financing management in the free education policy at the Ahmad Syamsul Ma'arif Langgongsari foundation and to find out what are the inhibiting factors and supporting factors in the management of the free education policy at the Ahmad Syamsul Ma'arif Langgongsari foundation. Theoretically, the benefit of this research is that it is an additional insight for researchers and readers related to financial management in free education policy. Practically, the benefit of this research for the author is as an additional insight into financial management in the management of free education policies. The benefit of this research for institutions is that it is hoped that this research can provide an overview for the development of institutions, especially in the field of financial management and education management. The approach used in the research is qualitative descriptive. The researcher conducted a deepening of various phenomena in the field and described them in the form of words and sentences. The subjects of the research taken were the person in charge of education, the manager of the foundation's business unit, and the students. The data collection methods used by the researcher are interviews, observations and documentation. The results of the research on Financial Management in the free education policy at the Ahmad Syamsul Ma'arif foundation are the source of the foundation's funds, namely from the pesantren business unit, donors and BOS funds. Bismis units belonging to Islamic boarding schools include Toya Enha, Warung Nyamplungan, Enha Barber, Enha Mart, Sate Wringin, Hebi Motor and Enha Madu. The financial manager of the foundation is the caregiver. The purpose of the free education policy made by caregivers is solely to help those who are less fortunate in the field of education. Enthusiasm.